SYNTHESIS OF FAUJASITE WITH HIGH THERMAL STABILITY FROM FLY ASH - Sutarno Sutarno; Yateman Arryanto (Indonesian Journal of Chemistry, 2004)
Faujasite was hydrothermally synthesized from fly ash at 100oC in alkaline solution by reflux with various concentration of HCl and fusion with NaOH (weight ratio of NaOH/fly ash = 1.2) pretreatments. Thermal stability of faujasite from fly ash was tested at 400-900oC and was compared with commercial zeolite Y. The solid products were characterized by X-ray diffraction method, chemical analysis and nitrogen adsorption (BET). Results showed that synthesis of faujasite from fly ash via fusion pretreatment with NaOH has resulted faujasite selectively, however, the faujasite obtained still showed relatively low thermal stability due to its relatively low of Si/Al mol ratio. Reflux pretreatment with HCl was an effective method not only to increase the Si/Al mol ratio but also to decrease the metal impurities in the fly ash sample. Synthesis of faujasite from fly ash via combination of reflux with HCl and fusion with NaOH pretreatment has resulted faujasite selectively with higher Si/Al mol ratio. Faujasite obtained from fly ash via combination of reflux with HCl and fusion with NaOH pretreatment showed thermal stability as high as commercial zeolite NaY.